Sosialisasi Pemetaan Geologi, Drainase Kawasan, dan Cekungan Air Tanah Guna Pencegahan Longsor di Kelurahan Sadeng - Agustinus Sungsang Nana Patria; Master Almoris Baene; Wahyu Okta Legowo; Rifa Fauziah; Alfonso Naser S. Reis Amaral; Wahyu Dwi Mardiani; Wilson Edy Rafael; Arjuna Muttho'an; Riyan Adi Saputra; Eka Wahyuningsih; Inna Fajrotul Bahiroh; Ira Sephiana Pangestuti; Thomas Azziz Alathif; Rifqi Tri Wahyu Ramadhan; Iffah Nur Hanifah; Muhamad Chairudin (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2024)
This article discusses the socialization activities of geological mapping, regional drainage, and groundwater basins (CAT) in Sadeng Village aimed at increasing public understanding of the conditions of their area in order to prevent landslides. This socialization involved various parties, including local agencies, academics, and community leaders, with a focus on geological conditions, drainage systems, and potential groundwater basins in the area. The methods used included field surveys, participatory mapping, and Focus Group Discussions (FGD) to identify geological conditions and major problems in the drainage system and groundwater management. The results of this activity showed that the community began to understand the conditions of the area, realized the importance of protecting the environment and was actively involved in improving the drainage system and groundwater management. The recommendations prepared included construction solutions according to the results of geological mapping, and improvements to drainage infrastructure. This socialization is expected to be a model for implementation in other areas with similar environmental characteristics.